Clustering OECD Countries According to Tax Indicators - Selim Tüzüntürk (International Journal of Public Finance)
This study aims to cluster a particular group of countries (OECD countries) according to tax indicators and to determine essential variables in clustering. The recent data on taxation percentages 2021 in OECD countries were obtained from the OECD website. Since the number of clusters was not known a priori, the hierarchical clustering analysis and two-stage clustering methods were used, and the findings of both methods were compared. Research findings show that OECD countries are classified into two meaningful clusters regarding statistically significant tax indicators (goods and services tax, personal income tax, and property tax) for both methods. The first cluster's goods and services tax average is lower than the second. The personal income tax average of the first cluster is higher than the second. The property tax average of the first cluster is higher than the second. The tax differences indicate that countries in the first cluster collect more personal income and property taxes but fewer goods and services taxes than countries in the second cluster, which points out the characteristics of developed countries in the scope of tax policies.